2 The role of 18F-FDG PET/CT imaging in the diagnosis of infective endocarditis. (May 2018) - Clay, Thomas; Primus, Christopher; Al-Khayfawee, Ahmed; Wong, Kit; Uppal, Rakesh; Das, Satya; Bhattacharyya, Sanjeev; Davies, Ceri; Woldman, Simon; Menezes, Leon
Abstract : Introduction: Diagnosing infective endocarditis (IE) is challenging. The modified Duke's criteria have shortcomings. European Society of Cardiology guidance (2015) suggests a potential role of 18 F-Fluorodeoxyglucose positron emission tomography (PET), based on class C evidence. There is a lack of data for native valve IE (NVE). Methods: Dual centre retrospective study of all patients with suspected IE, from 01/2010. Patients were classified as confirmed/probable/rejected IE pre- and post-PET, with incremental benefit assessed versus actual diagnosis. This was defined by surgical specimen or Endocarditis Team (MDT) consensus at least three months following index admission. Results: PET was undertaken in 71 patients from 2010 to date; 59 since the inception of the MDT in October 2015 (male=50; mean age 60.6 y (range 19–89)). At discharge, 27/39 (69%) had confirmed NVE and 21/32 (66%) confirmed prosthetic IE (PVE). 30/71 (42%) patients required surgical intervention with concomitant device extraction in 7. Whilst Staphylococcus was isolated in 30/71 (42%) patients, 22/71 (31%) were peripheral blood culture-negative. PET sensitivity, specificity, positive and negative predictive values were 72%, 100%, 67% and 100% respectively in NVE, and 84%, 54%, 70% and 73% in PVE. PET highlighted 12/71 (16.9%) patients as having an alternative non-cardiac source of infection. Receiver Operating Characteristic (ROC) curves showed incremental benefit of PET over Duke's criteria alone (AUC 0.875 vs 0.750, p=0.003) in NVE, though no difference in PVE (AUC 0.682 vs 0.613, p=0.649) compared to discharge diagnosis. Conclusion: PET has incremental value above modified Duke's criteria in diagnosing IE, especially in NVE. PET has reduced specificity in PVE, likely related to post-surgical uptake.